(untitled) (Paliativní medicína, 2024)
The presented article prresents to the readers an analysis of the topics covered by round tables for experts in the field of palliative care within the residential and field social services of the Moravian-Silesian Region. The organizers pointed out four areas of topics related to the reflection of good practice, the cooperation of social and health components within the institution and across organizations, communication with family members and the care plan at the end of the client’s life. The World Café method was used for data collection and the results were processed using thematic analysis. We believe that the ideas from the round tables can also be beneficial for other organizations that are interested in implementing palliative principles into general care within their facilities.